General characteristic, biotrofical survey and possible changing of wild life in the region of building Gotsotlinskaya HES and surraundings - G. S. Dzhamirzoev; G. M. Abdurahmanov; E. M. Musinova (Юг России: экология, развитие)
The article lists the materials of wildlife, biotopical curvey and possible changing in connection with the building and exploitation of Gotsatlinskaya HES in Daghestan.